Cetane Number Booster Additive for Diesel Fuel Synthesized from Coconut Oil - Nasikin, Mohammad; Arbianti, Rita; Azis, Abdul (Makara Journal of Technology, 2002)
To reduce NOx, SOx, HC, and particulates that produce because of using diesel fuel, can be done by increasing cetane number. One of methods is adding an additive to diesel fuel. 2-Ethyl Hexyl Nitrate (2-EHN) is a commercial additive that an organic nitrate. Making an additive in this research is used palm oil by nitration reaction that used HNO3 and H2SO4. Result of this reaction is methyl ester nitrate that has a structure looks like 2-EHN. IR spectra from research show that methyl ester nitrate is indicated by spectrum NO2 at 1635 cm-1. This result show that methyl ester nitrate can be synthesized by nitration reaction and yield is 74,84% volume. Loading 1% methyl ester nitrate to diesel fuel can increase cetane number from 44,68 to 47,49.